Answer:
Step-by-step explanation:
It seems you got the right answer, but didn’t do the problem correctly.
The square root of 2 times the square root of 2 is 2. And then 6 times the square root of two minus the product of 6 and the square root of two equals zero. And then obviously 6 and -6 equals -36. So 2+-36 is -34
Answer:
y=2x+1
Step-by-step explanation:
Parallel = gradients are the same
Example: y=2/4x+5
Perpendicular = gradients are the inverse of each other
Example: y= -4/2x+1
Any equation would be correct unless the gradient is 2/4 or -4/2
Answer:
<h3>B. 4units</h3>
Step-by-step explanation:
Find the diagram attached. The diagram is a similar triangle.
From the diagram, XZ/XY = CA/AB
Given XZ = 2x-2+2x-2 = 4x-4
XY =5x-7
CA = 2x-2
AB= x+1
On substituting this parameters into the formula to get x first
4x-4/5x-7 = 2x-2/x+1
cross multiply
(4x-4)(x+1) = 5x-7(2x-2)
open the parenthesis
4x²+4x-4x-4 = 10x²-10x-14x+14
4x²-4 = 10x²-24x+14
10x²-4x²-24x+14+4 = 0
6x²-24x+18 = 0
x²-4x+3 = 0
x²-3x-x+3 = 0
x(x-3)-1(x-3) =0
(x-3)(x-1) = 0
x = 3 and 1
Next is to get length AX.
Given AX = 2x-2
Substitute x = 3 into the expression
AX = 2(3)-2
AX = 6-2
AX = 4 units
Hence the measure of length AX is 4 units
Answer:
Step-by-step explanation:
A
2,400,000 is my answer (: I calculated it